Respiratory muscle training improves aerobic capacity and respiratory muscle strength in youth wrestlers - Tosun, Mehmet Ismail; Demirkan, Erkan; Kaplan, Abdurrahim; Ari Yilmaz, Yasemin; Eker Arici, Irem; Favre, Michael; Aslan, Veysi; Kutlu, Mehmet (Frontiers in Physiology, 2025)
BackgroundRespiratory muscle training (RMT) has shown potential for enhancing athletic performance, but its effectiveness, in youth wrestlers, remains unclear. This study aimed to investigate the effects of RMT on respiratory muscle strength and aerobic endurance in youth wrestlers.MethodsA parallel-grouperal was conducted across 22 male youth wrestlers aged 14.8 ± 0.4 years. Participants were assigned to an experimental(E) group (n = 11), which received RMT in addition to their regular wrestling training, or a control(C) group (n = 11), which continued with standard wrestling training only. The RMT was performed three times a week using the POWERbreathe Classic Blue® device at 50% of maximal inspiratory pressure (MIP). Pre- and post-intervention measurements included MIP, peak inspiratory flow (PIF), inspiratory volume (IV), and aerobic endurance assessed by the Yo-Yo Endurance Level 1 test (YYT).ResultsSignificant improvements were observed in the E group, with MIP increasing by 9.57%, PIF by 14.77%, and IV by 10.46% (p < 0.05 for all). Aerobic endurance, as measured by VO2max and total running distance, also significantly improved by 4.93% and 8.22%, respectively (p < 0.05). The C group showed smaller yet significant gains in MIP, PIF, and VO2max but no significant change in IV.ConclusionThe addition of RMT to traditional wrestling training significantly enhances respiratory muscle strength and aerobic endurance in youth wrestlers. These results suggest that RMT may be an effective complementary training method to improve athletic performance in this population.